Preliminary study of acute febrile response to crude LPS extract from Salmonella typhimurium in domestic chicken (Gallus gallus domesticus) AKY strain - Wijaya, Rizky Surya; Lelono, Asmoro; Oktarianti, Rike (Universitas Muhammadiyah Surakarta, 2026)
Salmonella is a genus that commonly attacks the health of poultry, especially chickens. One type of poultry that is widely attacked by S. typhimurium is chickens. S. typhimurium infects the host with Lipopolysaccharides (LPS). This study aims to determine the innate immune response of domestic chickens to LPS-based vaccines S. typhimurium as the first step in vaccine development. The sample was in the form of female domestic chickens of the AKY strain which was divided into 3 groups, the control group was injected using 0.1ml of PBS (Phosphate Buffer Saline) treatment group 1 was injected with LPS with an adjuvant with a concentration of 0.5mg/kg as much as 0.1ml. Treatment group 2 was injected with LPS with an adjuvant with a concentration of 1mg/kg of 0.1ml. Injection treatment group using Incomplete Freund Adjuvant (IFA). The results obtained were that the treatment groups had an increase in temperature at the 1st hour to the highest in the 3rd hour with a temperature range of 42.5°C to 42.6°C, contrast to the control group which has a static temperature with a range of 41°C to 41.8°C. The comparison of chicken body temperature among treatment groups using a Liner Mixed Model revealed a significant difference (p < 0.001) between the treatment groups and the control group. These results indicate that subcutaneous LPS administration induces a controlled acute febrile response, which is consistent with involvement of innate inflammatory pathways.